Efektivitas Model Pembelajaran Berbasis Proyek (Project-Based Learning) terhadap Keterlibatan Siswa di SMA Negeri 08 Kota Serang - Popi Dayurni; Ade Fricticarani; Kurniati Rahmadani; Siswandy Siswandy (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research was motivated by the low level of student involvement in the subject. Student engagement is often a major challenge. Lack of student engagement can be caused by various factors, such as learning methods that are less interesting and irrelevant to their needs. The research aims to see the effectiveness of the project-based learning model on student involvement. The method used in this research is quantitative. The results of this research show that the Project Based Learning Model has proven to be effective for Student Engagement at SMA Negeri 08 Serang City by proving the results of this research using a paired sample t test, the result of tcount is -36.256 on df 17. The basis for decision making is if tcount > ttable then H0 is rejected and Ha accepted. The ttable value in df 17 is 2.110. Thus, 36.256 > 2.110 means H0 is rejected and Ha is accepted, which means that the Project-Based Learning model is effective for student engagement. Then the magnitude of effectiveness is calculated by calculating the N-gain score test, the average value of the N-gain score is 70.7864 or 70.78%, which is in the high category.